Factors related to knowledge and perception of women about smoking: a cross sectional study from a developing country - Taj Fawad; Andrades Marie; Bhanji Seema; Khuwaja Ali K (BMC, 2011)
Abstract Background Smoking rates among women are currently low, but they are the fastest growing segment of cigarette smoking population in developing countries. We aimed to assess the knowledge and perceptions towards smoking and to identify the factors related with level of knowledge and perceptions among adult women in urban slums. Methods This was a cross sectional study conducted on 250 adult (≥18 years of age) women attending primary care clinics in three slums of Karachi, Pakistan. A pre-tested and structured, interviewer administered questionnaire was used for data collection. Factors associated with level of understanding about smoking were analyzed with chi-square test. Results Most of the women knew that smoking has adverse effects on women and children's health but the knowledge of specific health effects was limited. About one third of the women knew that active smoking can cause lung disease, but only a small percentage (7%) knew that it could lead to heart disease. None of the women were aware that smoking contributes to infertility and osteoporosis. A small proportion of women were aware that smoking can lead to low birth weight (7%), congenital anomalies (5%) and less than 1% of women knew that it contributes to pregnancy loss, still birth and preterm delivery. The understanding of passive smoking affecting children's lung was low (20%) and a similar proportion voiced concern about the bad influence of maternal smoking on children. Educated women had better knowledge of health effects of smoking. Education was associated with having better knowledge about effects on women health in general (p = 0.02) and specific effects like lung (p = 0.03) and reproductive health effects (p < 0.001). Education was also associated with knowledge regarding effects on fetus (p < 0.001) and children (p < 0.005). Although most of the women disliked being around smokers, more than one third thought that smoking decreases boredom (39%), tension (38%) and also helps to relax (40%). A large proportion (48%) of women had the misconception that smoking helps to reduce weight. Conclusions This study reveals that women are aware of the general ill effects of smoking but fail to identify smoking to be associated with female maladies particularly those who were illiterate and had lower levels of education. Understanding and attitudes needs to be improved by increasing health awareness and education of women in these urban communities with special emphasis on the effects of smoking on women's health.